Determination of β-Galactooligosaccharides (GOS) in Infant Formula and Adult Nutritionals: Single-Laboratory Validation, First Action 2021.01. (22nd July 2021) - Cuany, Denis; Andetsion, Fikrey; Fontannaz, Xavier; Bénet, Thierry; Spichtig, Véronique; Austin, Sean
Abstract: Background: β-Galactooligosaccharides (GOS) are typically used in infant formula and adult nutritionals as a source of nondigestible oligosaccharides, which may bring beneficial effects through modulation of the gut microbiota. However, suitable methods for the determination of GOS in products with a high background of lactose do not exist. Objective: The aim of this work was to develop a method suitable for the determination of GOS in infant formula and adult nutritionals and demonstrate suitability through single laboratory validation. Methods: Reducing oligosaccharides are labeled with 2-aminobenzamide (2AB), separated by hydrophilic interaction LC, and determined assuming that all oligosaccharides give an equimolar response in the detector. The same sample is analyzed a second time after treatment with β-galactosidase to remove GOS. The difference in the determined oligosaccharides between the two measurements will be the GOS content of the sample. The method was validated in a single laboratory on infant formula and adult nutritionals. Results: Recoveries were in the range 91.5–102%, relative standards of deviation (RSDr ) were in the range 0.7–5.99%, and one sample had an RSDr of 8.30%. Except for the one sample with an RSDr of 8.30%, the performance is within the requirements outlined in the Standard Method Performance Requirements, which specifies recoveries in the range 90–110% and RSDr of below 6%. Conclusions: The method is suitable for the determination of GOS in infant formula and adult nutritionals. Highlights: A method has been developed which is suitable for the determination of GOS in products with a high background concentration of lactose (infant fromula and adult nutritionals). The method does not require access to the GOS ingredient used for the production of the finished product. It is also possible to separately quantify the amount of GOS containing three or more monomeric units in order to support dietary fibre analysis.